Therapeutic Effect of Novel Cyanopyrrolidine-Based Prolyl Oligopeptidase Inhibitors in Rat Models of Amnesia - Zolotov, Nikolay N.; Schepetkin, Igor A.; Voronina, Tatyana A.; Pozdnev, Vladimir F.; Khlebnikov, Andrei I.; Krylova, Irina V.; Quinn, Mark T. (Frontiers in Chemistry, 2021)
Prolyl oligopeptidase (POP) is a large cytosolic serine peptidase that is altered in patients with Alzheimer’s disease, Parkinsonian syndrome, muscular dystrophies, and other denervating diseases. Thus, POP may represent a relevant therapeutic target for treatment of neuropsychiatric disorders and neurodegenerative diseases. Here, we report the characterization of five novel cyanopyrrolidine-based compounds (BocTrpPrdN, BocGlyPrdN, CbzMetPrdN, CbzGlnPrdN, and CbzAlaPrdN) and show that they are potent inhibitors of POP and are predicted to penetrate the blood-brain barrier (BBB). Indeed, we show that CbzMetPrdN penetrates the rat BBB and effectively inhibits POP in the brain when administered intraperitoneally. Furthermore, molecular modeling confirmed these compounds likely inhibit POP via interaction at the POP catalytic site. We evaluated protective effects of the cyanopyrrolidine-based POP inhibitors using scopolamine- and maximal electroshock-induced models of amnesia in rats and showed that BocTrpPrdN, BocGlyPrdN, CbzMetPrdN, and CbzGlnPrdN significantly prolonged conditioned passive avoidance reﬂex (CPAR) retention time when administered intraperitoneally (1 and 2 mg/kg) before evaluation in both models of amnesia, although CbzAlaPrdN was not effective in scopolamine-induced amnesia. Our data support previous reports on the antiamnesic effects of prolinal-based POP inhibitors and indicate on important role of POP in the regulation of learning and memory processes in the CNS..